A clinical study on ventral hernias in a tertiary care hospital - Chavan, Sushrut Subhash; Baruah, Tridip Dutta; C. P., Ganesh Babu (International Surgery Journal, 2017)
Background: Ventral hernias comprise the second most common hernia presentations in the surgical world. This study was undertaken to know the different clinical types, age incidence, predisposing factors for ventral hernia and also to study the post-operative results of different operative procedures. Methods: 250 cases of abdominal wall hernias were studied during the period of 3.5 years from January 2013 to June 2016. Out of which 150 cases were studied retrospectively from January 2013 to December 2014 with the help of the case sheets available in the MRD. The prospective study was done from January 2015 to June 2016 in which each patient was evaluated separately and thoroughly and his surgery planned so as to obtain satisfactory results. 69.6% were incisional hernias following an operation. 8% patients had presented with complications like irreducibility, obstruction and strangulation. The presence of associated diseases, large hernia, poor condition of local tissue (muscle), all make the surgical management of ventral hernia a complex problem. Either anatomical repair or Mesh repair were undertaken for all patients in this study. Results: Females were affected much more than the males. The proportion of females to males affected with ventral hernia was 5:1. Out of the three types of hernia that were studied only epigastric hernia showed more incidence in males whereas incisional and paraumbilical hernias were much more common in females. Most common age presentation was fourth and fifth decade. 92% of ventral hernias were uncomplicated at the time of presentation. In 100% of the cases swelling was the complaint followed by pain (18.8%). Previous surgery was the most common etiological factor in the development of ventral hernias (69.6%) followed by obesity (23.2%) In both groups mesh repair (63.6%) and anatomical repair (36.4%) there were no recurrences or deaths in the follow up period of 3 months. Conclusions: Ventral hernias are common surgical complaints. Prevention is the better treatment in the form of meticulous dissection and proper post-operative care to avoid incisional hernias. Presence of ventral hernia is an indication for surgery even in presence of co-morbid conditions like ascites, COPD, BPH as these patients are more prone for complications and of course these conditions need proper addressal. Mesh repair has nowadays become the standard of care but the results of the surgery depends upon the expertise of the surgeon.